Study on surface fatigue and metamorphic layer of raceway of hybrid ceramic ball bearing in high-speed spindle for machine tool. (January 2023) - Zhang, Xiaochen; Wu, Di; Xia, Zhuofan; Li, Yifeng; Wang, Jianqiu; Han, En-Hou
Highlights: A metamorphic layer forms on the upper surface of the bearing raceway under the cyclic contact stress. Stress-induced effect plays an important role in the transformation from the common martensite structure to the metamorphic layer. Under the cyclic contact stress, the dislocation pile-up groups form in carbide particles, and the carbide particles can even be elongated and crushed. The cracks initiate and propagate near the metamorphic layer, which leads to the peeling band, the surface fatigue damage and premature failure of the precision bearings. Abstract: Performance degradation of the precision bearing originates from the surface fatigue damage, which results in the premature failure of precision bearings in high-end spindle for machine tool. A metamorphic layer forms on the upper surface of the bearing raceway under the cyclic contact stress. The microstructure of the metamorphic layer is consisted of the nanocrystalline layers paralleled to the surface of the raceway. Stress-induced effect plays an important role in the transformation from the common martensite structure to the metamorphic layer, i.e., the grain refinement. Under the cyclic contact stress, the dislocation pile-up groups form in carbide particles, and the carbide particles can even be elongated and crushed. The cracks initiate and propagate near the metamorphic layer, which lead to the peeling band, the surface fatigue damage and premature failure of the precision bearings. This finding indicates that one solution to mitigating the surface fatigue in bearing might be the surface technology application.